The Trans-Urals in S.U. Remezov’s Atlases: Systematization of Settlement Patterns and Functional Purpose of Maps based on the Initial Development of the Tobol-Irtysh Region at the turn of the 17th and 18th centuries - Vladimir M. Kostomarov; Kirill Y. Krestyannikov; Vladislava O. Isaeva; Darya V. Kozlova (Журнал Фронтирных Исследований)
The article attempts to examine the entire corpus of S. U. Remezov’s geographical heritage. His world-renowned works are often used as sources for various studies of Siberia of the Petrine era; however, comparative analyses of geographical and source study potential are rarely conducted, as existing methods of source analysis generally rely on historical approaches. In our study we attempted to approach the typology and functional purpose of Remezov’s maps through the lens of analyzing geographical and historical data contained within them. We also tried to verify basic hypotheses about settlement patterns in the Trans-Urals at the turn of the 17th and 18th centuries. Basing on the research materials, the authors were able to evaluate several strategies of settlement and territorial development. Additionally, the article proposes several methods of evaluating cartographic sources and discusses various issues related to the functional purpose of S. U. Remezov’s atlases, providing fairly prolific historiography. The main provisions and concussions of the paper may be of interest to historians specializing in historical geography and the history of Russian cartography at the turn of the 17th and 18th centuries.